Detecting and characterising an englacial conduit network within a temperate Swiss glacier using active seismic, ground penetrating radar and borehole analysis. Issue 79 (September 2019) - Church, Gregory; Bauder, Andreas; Grab, Melchior; Rabenstein, Lasse; Singh, Satyan; Maurer, Hansruedi
ABSTRACT: Englacial hydrology plays an important role in routing surface water to the glacier's bed and it consequently affects the glacier's dynamics. However, it is often difficult to observe englacial conduit conditions on temperate glaciers because of their short-lived nature. We acquired repeated active surface seismic data over the Rhone Glacier, Switzerland to monitor and characterise englacial conduit conditions. Amplitude-versus-angle analysis suggested that the englacial conduit is water filled and between 0.5 and 4 m thick. A grid of GPR profiles, acquired during the 2018 melt season, showed the englacial conduit network persisting and covering ~ 14, 000 m 2 . In late summer 2018, several boreholes were drilled into the conduit network. We observed generally stable water pressure, but there were also short sudden increases. A borehole camera provided images of a fast flowing englacial stream transporting sediment through the conduit. From these observations, we infer that the englacial conduit network is fed by surface meltwater and morainal streams. The surface and morainal streams merge together, enter the glacier subglacially and flow through subglacial channels along the flank. These subglacial channels flow into highly efficient englacial conduits traversing the up-glacier section of the overdeepening before connecting with the subglacial drainage system.